2009
DOI: 10.1158/1055-9965.epi-08-0696
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibody to Tumor Antigen, Alpha 2-HS Glycoprotein: A Novel Biomarker of Breast Cancer Screening and Diagnosis

Abstract: We sought to identify a new serum biomarker for breast cancer screening and diagnosis using stepwise proteomic analysis of sera from breast cancer patients to detect the presence of autoantibodies that react with urinary protein. Two-dimensional immunoblotting was done for screening autoimmunogenic tumor antigens in the urine of breast cancer patients. Reactive spots were identified by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. Among urinary proteins separated by twodimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 44 publications
(35 reference statements)
1
47
0
Order By: Relevance
“…They are biochemically well-characterized, and many reagents and techniques are available for their detection, simplifying assay development. Until very recently, several specific autoantibodies have been detected in the sera of patients with advanced-stage breast cancer (14,(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58). However, very few studies have attempted to identify and/or evaluate autoantibodies in node-negative earlystage PBC ( 2 cm) or, more importantly, in preinvasive breast cancer, for which mammography's sensitivity is decreased.…”
Section: Discussionmentioning
confidence: 99%
“…They are biochemically well-characterized, and many reagents and techniques are available for their detection, simplifying assay development. Until very recently, several specific autoantibodies have been detected in the sera of patients with advanced-stage breast cancer (14,(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58). However, very few studies have attempted to identify and/or evaluate autoantibodies in node-negative earlystage PBC ( 2 cm) or, more importantly, in preinvasive breast cancer, for which mammography's sensitivity is decreased.…”
Section: Discussionmentioning
confidence: 99%
“…78), and NY-ESO-1 (79) were first discovered in patients with breast cancer. In fact, antibodies to HER2/neu (76) have been detected in patients with early-stage breast cancer but their presence has also been detected in other cancers, limiting their use as a diagnostic biomarker for breast cancer alone (28,30,80). An increase to 44% sensitivity and 97.6% specificity in breast cancer detection was achieved through the successive addition of the three TAAs p53, protein 16 (p16), and avian myelocytomatosis viral oncogene homolog (c-myc; ref.…”
Section: Breast Cancermentioning
confidence: 99%
“…The study found HSP60 autoantibodies in 47.5% of patients with breast cancer and in only 4.7% of healthy control sera. a-2-HS-glycoprotein (AHSG) autoantibodies have also been identified in 79.1% of 81 breast cancer patient samples and only in 9.6% of 73 control samples; however, the diagnostic relevance of these autoantibodies remains to be validated (80).…”
Section: Breast Cancermentioning
confidence: 99%
“…Major protein depletion, solution isoelectric focusing, and 1D PAGE resulted in 575 and 2,890 protein identifications from plasma and serum, respectively . Identifying the targets of immune reactions to proteins from cancer cells, normal self cells, and bacteria has been greatly facilitated by the use of PAGE followed by immunological probing with patient sera and mass spectrometry (Brichory et al, 2001;Hong et al, 2006;Pereira-Faca et al, 2007;Basagana et al, 2008;Bunk et al, 2008;Desmetz et al, 2008;Fujita et al, 2008;Hamrita et al, 2008;Nagashio et al, 2008;Taylor et al, 2008;Zhong et al, 2008;Kim et al, 2008b;Liu et al, 2008b;Forgber et al, 2009;He et al, 2009;Patwa et al, 2009;Rao et al, 2009;Shimada et al, 2009;Tamesa et al, 2009;Yi et al, 2009). A large number of protein isoforms in serum, or EDTA versus citrated plasma, were detected by fluorescent labeling prior to separation of the intact proteins by charge, hydrophobic character and molecular mass (Misek et al, 2005).…”
Section: E One-dimensional Poly Acrylamide Gel Electrophoresis (1d Pmentioning
confidence: 99%